Tobacco Smoking Was Positively Associated with Disease Relapse at week 24 and 48 Among Patients with Psoriasis Vulgaris in Shanghai: A Prospective Study - Shen F; Ding Y; Qiang Y; Duan Z; Xu Q; Gao X; Zhang R; Wang R (Psoriasis: Targets and Therapy, 2025)
Fanlingzi Shen,1,2,* Yuning Ding,1,* Yan Qiang,1,* Zhen Duan,2 Quanruo Xu,2 Xiangjin Gao,1 Rui Zhang,1 Ruiping Wang1,2 1Clinical Research Center, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2School of Public Health, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ruiping Wang, Clinical Research Center, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, 1278 Baode Road, Shanghai, 200443, People’s Republic of China, Email w19830901@126.comPurpose: Tobacco smoking is an unhealthy behavior associated with the onset, severity, and treatment response of psoriasis. However, evidence regarding the impact of tobacco smoking on the relapse of psoriasis remains limited. This study aims to examine the relapse condition in psoriasis patients and explore the association between tobacco smoking and psoriasis relapse.Patients and Methods: We conducted an observational study with 551 psoriasis patients recruited from 2022 to 2024 in Shanghai Skin Disease Hospital. A structured questionnaire and physical examination were used to collect data at baseline, week 12, week 24 and week 48. PASI50 and PASI75 were used to evaluate the improvement of psoriasis patients after treatment at week 12, and disease relapse was defined as the loss of 50% PASI improvement during clinical remission after the achievement of PASI50 or PASI75 at week 12.Results: 75.7% of the 551 psoriasis patients were males, with an average age of 45.8 years, and 282 (51.2%) were tobacco smokers. 41.2% and 61.6% of psoriasis patients with PASI50 achievement at week 12 encounter disease relapsed at week 24 and 48, respectively, while for patients with PASI75 achievement at week 12, the relapse rate was 27.6% and 51.7% at week 24 and 48, respectively. Logistic regression indicated that patients with tobacco smoking had a higher relapse rate, especially among those with PASI75 achievement at week 12. The odds ratio was 2.10 (95% CI: 1.17– 3.78) and 1.84 (95% CI: 1.07– 3.14) at week 24 and week 48 respectively, even after adjusting for potential confounding factors. Moreover, patients with longer smoking duration and more daily cigarette consumption had higher relapse rate.Conclusion: Tobacco smoking was positively correlated with the relapse, especially among those with longer smoking duration and more daily cigarette consumption. Therefore, patients with psoriasis should quit smoking to reduce the risk of relapse.Keywords: psoriasis, tobacco smoking, relapse, psoriasis area severity index, PASI